The Influence of Digital Marketing Use with Electronic Word Of Mouth (E-Wom) as Mediation in Tourist Visit Interest at Taman Balekambang Surakarta - Sadewa, Alfirdaus Ari; Pratama, Sandyawan Artha; Budianto, Dimas Tanggu; Alrafsanjani, Muhammad; Ramadhan, David; Zakiya, Nadiya Fikriyatuz (Nirta Learning Centre, 2025)
This study aims to explore and analyze the influence of digital marketing usage on tourists’ visit intention, with electronic word of mouth (E-WOM) as a mediating variable at the Taman Balekambang tourism destination in Surakarta. Taman Balekambang is one of the city’s iconic tourist attractions with historical, cultural, and ecological value, yet it still faces challenges in attracting an optimal number of visitors amid increasingly intense competition among tourist destinations. Alongside the development of information technology and changes in tourists’ information consumption patterns, digital marketing strategies have become essential tools to reach a broader market. On the other hand, E-WOM serves as a vital element that strengthens the credibility of promotional messages through reviews and experiences shared by previous visitors via social media and other digital platforms. This study uses a qualitative descriptive approach with data collection techniques including direct observation of digital promotion activities conducted by the management, documentation from social media, and relevant literature analysis. The results show that digital marketing significantly contributes to increasing destination visibility through the dissemination of visual content, event information, and interaction with prospective tourists. Furthermore, E-WOM proves to play a mediating role in strengthening the influence of digital marketing on tourists’ visit intention, through testimonials, comments, and positive reviews that encourage visitation decisions. These findings support previous research indicating that the synergy between digital promotion and consumer communication positively impacts tourist visitation behavior.The implications of this study not only enrich the digital marketing literature in the tourism context but also provide practical recommendations for tourism destination managers to develop more participatory and responsive digital strategies to meet tourists’ informational needs.